Halogen Bonding Provides Heterooctameric Supramolecular Aggregation of Diaryliodonium Thiocyanate; Crystals; Vol. 10, iss. 3 - Soldatova L. A. Nataljya Sergeevna; Suslonov V. V. Vitaly Valerjevich; Kissler T. Yu. Troyana; Ivanov D. M. Daniil; Novikov A. S. Alexander; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Postnikov P. S. Pavel Sergeevich; Kukushkin V. Yu. Vadim (2020, 2020)
Title screen